An analysis of the offences under the computer crimes act 1997 / Ahmad Kamal Roslan, Syazana Abd. Lajis and Maria ak Ugak - Roslan, Ahmad Kamal; Abd. Lajis, Syazana; Ugak, Maria (2006)
In 1997, the government of Malaysia has made a drastic move by introducing the first of its kind cyber laws of Malaysia as a result of the extensive development of Information, Communication and Technology (ICT) in Malaysia through the ambitious creation of the 'Asia's Silicon Valley', i.e. the Multimedia Super Corridor. The cyber laws of Malaysia consist of the: (1) Computer Crimes Act 1997; (2) Digital Signature Act 1997; and (3) Telemedicine Act 1997. Promising as this may sound, the public are nevertheless skeptical on the enforcement of the said Acts as until today, only the Computer Crimes Act 1997 has been gazetted while the other two remain silent. The purpose of the said Acts is to govern the usage of Information Technology (IT) especially in the cyber world. For example, the Computer Crimes Act 1997 provides a mean of protection to the Internet users, from the threats of activities of computer criminal such as computer virus and hacking. It is hope that this thesis will give an idea to the public generally and law students especially on the major offences and the adequacy of the penalties under the Computer Crimes Act 1997.